2016
DOI: 10.1097/md.0000000000005124
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound screening for neoplasms in children up to 6 years old

Abstract: The aim of the ultrasound (US) screening program was to detect neoplastic lesions in children, together with other pathologies of the developmental age in the area of the neck, abdomen, female pelvis, and scrotum in boys.US screening scans, including cervical, abdominal, pelvical, and scrotal US, were performed in the population of asymptomatic children aged from 9 months to 6 years. The children were scanned in Mobile Pediatric US Unit, consisting of 2 independent consulting rooms.The scans of 14,324 children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…This is very important for appropriate prenatal management of pregnancy and delivery in order to facilitate prompt postnatal treatment (26). Similarly, ultrasound screening in pediatric population can be used to reveal lesions like tumors or other pathologies of developmental age that are undetectable by clinical examination, before the onset of clinical symptoms (27,28). This is particularly appropriate for patients with cancer predisposition, for example, in children with BWS (27,29).…”
Section: Discussionmentioning
confidence: 99%
“…This is very important for appropriate prenatal management of pregnancy and delivery in order to facilitate prompt postnatal treatment (26). Similarly, ultrasound screening in pediatric population can be used to reveal lesions like tumors or other pathologies of developmental age that are undetectable by clinical examination, before the onset of clinical symptoms (27,28). This is particularly appropriate for patients with cancer predisposition, for example, in children with BWS (27,29).…”
Section: Discussionmentioning
confidence: 99%
“…While Edmund et al concluded that screening patients with a high risk of WT did not significantly improve survival, unscreened patients are said to present at a later stage [ 12 ]. Smaller tumours found due this “aggressive” screening strategy are also more amenable to renal sparing surgery [ 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite promising results that showed changes in approximately 25% of the examined children, these studies have not been introduced to the entire population. Another attempt was made by the RMHC Chapter in Poland, which purchased a special mobile ambulance equipped with two ultrasound rooms for pediatric ultrasound examinations [14]. These studies were cofinanced with local self-governments.…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of abnormalities were related to scrotal pathologies. Undescended testes and microlithiasis can affect testis growth and are proven conditions predisposing to the cancer occurrence [14,16].…”
Section: P R E P R I N Tmentioning
confidence: 99%